LIPASE ACTIVITY DURING LARVAL DEVELOPMENT OF AN INSECT, LEUCINODES ORBONALIS (GUEN EE) - GE JAGE, RAMESH. M.; GEJAGE, MANSHA R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
The brinjal fruit borer, Leucinodes Orbonalis (Guenee) is an important pest of eggplant in South Asia. Lipase activity during larval development of an insect, L. Orbonalis have been studied. The larval lipase revealed optimum pH 7.8, incubation time 30 minutes, temperature 37°C, enzyme concentration 1% and Substrate concentration 5%. The gradual increase in larval lipase activity was observed from 1-day old larvae to 8-day old larvae and gradual decrease from 8-day old larvae to 11-day old larvae. The maximum lipase activity was observed in 8-day old larvae. The physiological role of lipase during larval development of L. Orbonalis (Guenee) has been reported in present paper.